Conjugate Variability of Signs of the Female Generative System of Scots Pine (Pinus sylvestris L.) in the Conditions of Magnesite Pollution - Mohnachev, Pavel; Makhniova, Svetlana; Menshikov, Sergey; Pospelova, Nadezhda; Zavyalov, Konstantin; Ayan, Sezgin (Prensip Publishing, 2023)
In the conditions of environmental pollution by emissions of magnesite production (Combined Magnesite, Satka, Chelyabinsk region), a study of the conjugate variability of signs of the female generative system of the Scots pine (Pinus sylvestris L.) was carried out. Signs with a stable connection have been identified, as well as signs whose direction of interconnection changes under the influence of aerotechnogenic pollution. Thus, the relationship of the signs characterizing the size and mass of cones is rigidly genetically determined and is not violated in conditions of a strong level of pollution. The seed productivity of the pine stands, regardless of the growing conditions, is more closely related to the survival rates of ovules in the gametophytic period than in the period of embryonic development. However, in conditions of heavy pollution, the relationship between the survival of ovules in the 1st vegetative and embryonic periods is negative, which may indicate the effective elimination of abnormal gametophytes and the release of the stand from them in conditions of pollution. The strong weakening of trees and the low availability of mineral resources in conditions of high pH of the growing medium in the zone of heavy pollution cause an increase in the negative relationship between seed productivity and seed weight to a significant level. Also, the conditions of heavy pollution “contributed” to the development of a strategy of trees for the formation of small seeds with high quality and quality indicators, seedlings developed. Only in these growing conditions, with a decrease in seed weight, the indicators of germination energy, germination percentage, and morphometric indicators of seedlings significantly increased.
Keywords: 13. Climate action; 15. Life on land